MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA PENERAPAN MODEL KONTEKSTUAL, PENDEKATAN RME KELAS VI SD (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
This research was conducted using action research methods class . The background of this research is the fact on the ground that indicates the low value of student learning outcomes . By using a realistic model of the learning of mathematics in sixth grade writers strive to improve student achievement outcomes and learning mathematics less desirable student learning , especially in mathematics , so as to increase the interest of students towards math .To obtain information using the instrument , ie tests , worksheets , questionnaires , interview guides , and mathematics observasi.Pembelajaran sheet using a realistic model is done in groups .Based on the above results , it appears that all students increased math achievement results on the subject of arithmetic operations with fractions using the realistic method . This ditujunkkan with an average rating of students on the pretest and posttest respectively by 7.58 and 7.90 . Apparently there is an increase of 0.32 . The highest score on the posttest is 10 by 21 and a low of 6 people 7 people .Students' interest in learning mathematics can be seen from the results of the processing of student questionnaire . Almost all of the students expressed very attractive with realistic learning model and want another material was taught . Almost all students felt compelled to find it easier to learn and understand the material by using this realistic model of learning . Most of the students feel happy and satisfied with the results obtained after following the learning of mathematics by using a realistic model of learning .Based on the results it is concluded that the teaching and learning activities are carried out in the sixth grade SDN Duri Kosambi, West Jakarta 03 Evening actively underway , good and successful